COMMUNITY-BASED TOURISM DESTINATION MANAGEMENT IN SOMBU TOURISM VILLAGE, WAKATOBI - Devy Dwi Fajri (Jurnal REP (Riset Ekonomi Pembangunan), 2023)
Wakatobi is one of priority destinations in Indonesia that is famous for its beauty of underwater paradise. Most of its tourism destinations are managed using community-based tourism concept and one of them is Sombu tourism village in which its management is done by several community organizations and the village headman. However, its tourism activities haven’t showed significant increase that is seen from the low number of tourists visit to the village. Descriptive qualitative approach was applied in this research and the data was collected through observation, interview, and focused-group discussion which later validated using data triangulation. The result showed that there has not been any structured tourism village’s management organization since the village was established. This causes the unclear of task and responsibility of village’s managers. Current tourism management is performed separately by several community organizations and the village headman. Therefore, tourism destination management which can unite tourism managers to synergize is necessarily needed by the village, so the aim of tourism management to elevate social welfare can be achieved.